Nail Disorders in Systemic Diseases: A literatur Review - Faranajhia, Hagia; Maolidi, Juan; Rabbani, Muhammad Afif; Agusta, A. A. Gede Agung Difa; Rizky, Muhammad Ilham; Madani, Ayda Fitri; Dwiputri, Adelya Rahma; Ramadhani, Dhea Asty; Zakiyyah, Luthfi; Putri, Ajeng Ayu; Amatullah, Tazkiyah Arafah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Nail disease is a disorder that affects the structure and health of human nails. Nail disease associated with systemic disease can occur in various age groups and populations. The prevalence and incidence vary depending on the associated systemic disease. The purpose of writing this article is to provide new insight into the importance of understanding and identifying abnormal nail conditions as an early clue to underlying systemic disease so that it can provide benefits in improving early detection, appropriate treatment, and holistic disease monitoring. This article will focus on examples such as clubbing finger, koilonychia, yellow nail, and Leukonychia which have links to systemic diseases or disorders. Data sources were taken by conducting an electronic search through library search sites including Google Scholar, ProQuest, MDPI, and PubMed to search for articles discussing